THEORIES OF REGIONAL SECURITY AND THE STRATEGIC POSITION OF CENTRAL ASIA: UZBEKISTAN'S CONTRIBUTION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the evolution of the concept of regional security and its theoretical classification, with a particular focus on the Copenhagen School and alternative paradigms in international relations. Special emphasis is placed on the concepts of securitization, regional security complexes, and the influence of constructivist and postcolonial approaches in analyzing regional threats. The paper further explores the role of Central Asia in the contemporary architecture of regional security through the lens of Uzbekistan's position as an active and autonomous actor in international affairs. Based on the analysis of ongoing developments, the study highlights Uzbekistan's consistent efforts to promote regional cooperation, peaceful conflict resolution, and institutional collaboration, thereby contributing to the emergence of a favorable regional order amidst multifaceted global security challenges.